A Highly Efficient Chemiluminescence Probe for the Detection of Singlet Oxygen in Living Cells. Issue 39 (16th August 2017) - Hananya, Nir; Green, Ori; Blau, Rachel; Satchi‐Fainaro, Ronit; Shabat, Doron
Abstract: Singlet oxygen is among the reactive oxygen species (ROS) with the shortest life‐times in aqueous media because of its extremely high reactivity. Therefore, designing sensors for detection of 1 O2 is perhaps one of the most challenging tasks in the field of molecular probes. Herein, we report a highly selective and sensitive chemiluminescence probe (SOCL‐CPP ) for the detection of 1 O2 in living cells. The probe reacts with 1 O2 to form a dioxetane that spontaneously decomposes under physiological conditions through a chemiexcitation pathway to emit green light with extraordinary intensity.SOCL‐CPP demonstrated promising ability to detect and image intracellular 1 O2 produced by a photosensitizer in HeLa cells during photodynamic therapy (PDT) mode of action. Our findings makeSOCL‐CPP the most effective known chemiluminescence probe for the detection of 1 O2 . We anticipate that our chemiluminescence probe for 1 O2 imaging would be useful in PDT‐related applications and for monitoring 1 O2 endogenously generated by cells in response to different stimuli. Abstract : Illuminating singlet oxygen : A chemiluminescence probe for singlet oxygen based on dioxetane formation is described. The dioxetane decomposes through a highly efficient chemiexcitation process to emit green light. The probe was used to detect and image intracellular 1 O2 produced by a photosensitizer in HeLa cells during photodynamic therapy.